A Monolithic 622MB/S Half Rate Clock And Data Recovery Circuit Utilizing A Novel Linear Phase Detector. - Chen, Hau Jiun; Azni Zulkifli, Tun Zainal; Abdul Aziz, Zulfiqar Ali; Mohd Noh, Norlaili (2004)

(untitled)
Clock and data recovery (CDR) circuits are crucial components in high speed transceivers. In order to ensure synchronization between data and clock in the most economic way, clock information is embedded into the transmitted data stream.